Soil arthropods associated with sweetpotato crop (Ipomoea batata L.) in La Molina, Lima, Peru - Livia-Tacza, C. (2020)
Sweetpotato (Ipomoea batata L.) is an economically important crop grown in Peru. The present study aimed to determine the soil arthropods associated with sweetpotato and its relative abundance in sweetpotato production fields in La Molina, Lima, Peru. Evaluations were conducted at Universidad Nacional Agraria La Molina, from February to August 2017. Samples were collected using pitfall traps and examined at the Klaus Raven Büller Entomology Museum. Soil morphospecies were extracted and separated from collected samples and then counted, recorded and identified. They were also admitted to the Entomology Museum collection. Eighty morphospecies in the classes Collembola, Insecta, Malacostraca, Arachnida and Chilopoda of phylum Arthropoda were recorded. Within the Collembola class, Entomobryidae was the most abundant family; within Insecta, Gryllus spp. (Gryllidae); within Malacostraca, Porcellio laevis (Porcellionidae); within Arachnida, Theridion volubile (Theridiidae) of the order Aranea; and within Chilopoda, the order Lithobiomorpha. By understanding the diversity of arthropods, it may inform future measures and improve control of pests by taking into consideration the soil arthropods among which important beneficial natural enemies could be found.